ISOLATION, IDENTIFICATION AND MOLECULAR CHARACTERIZATION OF XYLANASE PRODUCING STREPTOMYCES SP FROM MARINE ECOSYSTEMS - SIVAKUMAR S; SHARMAL KUMAR M (International Journal of Pharma and Bio Sciences, 2016)
Xylanase produced by microorganisms has many applications in the pulp and paper industry. Xylanase are used in bleaching process where the chlorine and hypochlorine were used which acts as a major pollutant in this industry. Xylanase are also used in food and feed industry for the clarification of juice, to improve the coffee and tea extraction. The present study was carried out to isolate the actinomycetes that produce xylanase. Out of the 50 isolates, 10 were found to produce xylanase. Out of these, one isolate showed maximum enzyme activity that was identified as Streptomyces sp. using 16s rDNA sequencing. Among the different carbon source, organism grown in wheat bran showed maximum enzyme activity. Urea and peptone were the best nitrogen source for maximum enzyme activity. The effect of different temperature and pH on xylanase production was studied. Maximum level of xylanase activity was observed at temperature 30-60ºC, pH 6.0-7.0.